Diversidade genética em linhagens avançadas de soja oriundas de cruzamentos biparentais, quádruplos e óctuplos - Ferreira Junior, Jose Arantes [UNESP]; Uneda-Trevisoli, Sandra Helena [UNESP]; Coelho Goncalves Espindola, Sybelli Magda [UNESP]; Vianna, Viviane Formice [UNESP]; Di Mauro, Antonio Orlando [UNESP] (Univ Federal Ceara, Dept Geol, 2015)
The aim of this study was to analyse the genetic diversity and agronomic performance of a group of advanced and superior strains of soybean, derived from biparental, four-way and eight-way crosses, in order to identify future promising and superior combinations. The experiment was carried out in the experimental area of the Paulista State University, Julio de Mesquita Filho, Jaboticabal Campus, in the state of Sao Paulo, Brazil. The characteristics under evaluation were: number of days to flowering, plant height at flowering, number of days to maturity, plant height at maturity, height of the first pod, number of branches, number of pods per plant, agronomic value, lodging, one hundred seed weight and seed yield., The Mahalanobis distance and the relative contribution of each characteristic were used to calculate the phenotypic distances. Among the genotypes analysed, 19 strains displayed high productivity, being superior to the controls (V-max, CD 216, CD 219 and Conquista). The greatest distance found was between strains JAB 41 and JAB 17 (279.81), followed by JAB 40 and JAB 17 (261.38) and between JAB 40 and JAB 22 (255.46). There were six groups formed using the Ward method, indicating the presence of genetic variability among the tested strains. Increasing the number of parents had no effect on the increase in genetic diversity between the strains, and was not the factor responsible for the grouping or not of the genotypes under test.

O objetivo do presente trabalho foi analisar a diversidade genética e o desempenho agronômico de um grupo de linhagens avançadas e superiores de soja, oriundas de cruzamentos biparentais, quádruplos e óctuplos, para identificar futuras combinações superiores e promissoras. O experimento foi conduzido na área experimental da Universidade Estadual Paulista "Júlio de Mesquita Filho", Campus de Jaboticabal, São Paulo. Os caracteres avaliados foram: número de dias para floração, altura da planta na floração, número de dias para maturidade, altura da planta na maturidade, altura de inserção da primeira vagem, número de ramos, número de vagens por planta, valor agronômico, acamamento, peso de cem sementes e produtividade de grãos. Para o cálculo das distâncias fenotípicas foi utilizada a distância generalizada de Mahalanobis e a contribuição relativa de cada caráter. Dentre os genótipos analisados, 19 linhagens obtiveram altos rendimentos, sendo superiores às testemunhas (V-max, CD 216, CD 219 e Conquista). A maior distância encontrada foi entre as linhagens JAB 41 e JAB 17 (279,81), seguidas por JAB 40 e JAB 17 (261,38) e entre JAB 40 e JAB 22 (255,46). Verificou-se a formação de seis grupos pelo agrupamento de Ward, indicando a presença de variabilidade genética entre as linhagens avaliadas. O aumento do número de genitores não foi determinante para o aumento da diversidade genética entre as linhagens, bem como não foi o fator responsável pelo agrupamento ou não dos genótipos avaliados.
Genetic diversity in advanced soybean strains derived from biparental, four-way and eight-way crosses
Keywords: Glycine max; Dissimilarity; Productivity; Ward; Glycine max; Dissimilaridade; Produtividade; Ward